Functional disability and utilisation of long-term care in the older population in England: a dual trajectory analysis. - Hu, Bo; Cartagena-Farias, Javiera; Brimblecombe, Nicola (European Journal of Ageing, 2022)
This study investigates the developmental trajectories of long-term care needs and utilisation in older people aged 65 years and over in England. The data came from the English Longitudinal Survey of Ageing (ELSA, waves 6–9, 2012–2018, N = 13,425). We conducted dual trajectory analyses to cluster people's trajectories of care needs (measured by functional disability) and utilisation into distinct groups. We conducted logistic regression analyses to identify the factors associated with trajectory memberships. We identified three trajectories of long-term needs (low, medium, and high) and three trajectories of care utilisation (low, medium, and high). Both care needs and care hours increased with age, but the speed of increase varied by trajectory. Females, minority ethnic groups, people with low wealth, and those experiencing housing problems were more likely to follow the joint trajectories characterised by higher care needs and higher care intensity. People with low or medium care needs stayed in the same trajectories of care utilisation. In contrast, people in the high-needs trajectory followed divergent trajectories of care utilisation: 63% of them followed the trajectory of high care intensity and the rest (37%) followed the trajectory of medium care intensity. Lack of spouse care was the leading predictor of trajectory divergence (OR = 3.57, p < 0.001). Trajectories of care needs and utilisation are highly heterogeneous in later life, which indicates persistent inequalities over time. Single people with multiple functional limitations face an acute and enduring risk of inadequate care and unmet needs. The amount of support is as important as the availability of support.